PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL KABUPATEN BENGKALIS - Billy Yanis Saputra; Firdaus Firdaus; Imam Fakhruddin; Riki Rianto; Putri Neli Pratiwi; Nurhayati Nurhayati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
For more than two years, Bengkalis Regency has become an autonomous region, but it has not been able to independently from the financial aspect to run the wheels of government. Characterized by the small contribution of PAD to APBD and still high dependence on the Balance Fund from the central government. This research aims to find out how the effect of balance funds and local native income on the capital expenditure of Bengkalis Regency. The population in this study is the Budget Realization Report (LRA) of Bengkalis Regency in 2012-2021, the sampling technique used is census. Data is processed by multiple linear regression. The results showed that the balance fund had no effect on capital expenditures. This is due to the lack of optimal use of regional budgets, where the amount of silpa funds every year. This silpa fund, shows the weakness of the Local Government in the absorption of budgets for activities that support the economic improvement of the community so that the large funds cannot be realized in the form of capital expenditure optimally. The original income of the region has a negative but insignificant effect on capital expenditure. This is due to the low realization of PAD so as to reduce capital expenditure. Where PAD as one of the sources of regional revenue will determine the size/small capital expenditure.